2013
DOI: 10.1096/fj.13-236372
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic sensors FXRα, PGC‐1 α, and SIRT1 cooperatively regulate hepatitis B virus transcription

Abstract: Hepatitis B virus (HBV) genome transcription is highly dependent on liver-enriched, metabolic nuclear receptors (NRs). Among others, NR farnesoid X receptor α (FXRα) enhances HBV core promoter activity and pregenomic RNA synthesis. Interestingly, two food-withdrawal-induced FXRα modulators, peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) and deacetylase SIRT1, have been found to be associated with HBV genomes ex vivo. Whereas PGC-1α induction was shown to increase HBV replication, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…For example, multiple transcription factors associated with hepatic metabolic processes, including HNFs, [244, 245] peroxisome proliferator-activated receptors (PPARs), [245247] and FXR [248250] can all be recruited to the HBV genome. [33] Moreover, studies in vitro have shown that exogenous addition of bile acids to HBV-expressing cells can increase HBV replication.…”
Section: Hbv and Hccmentioning
confidence: 99%
“…For example, multiple transcription factors associated with hepatic metabolic processes, including HNFs, [244, 245] peroxisome proliferator-activated receptors (PPARs), [245247] and FXR [248250] can all be recruited to the HBV genome. [33] Moreover, studies in vitro have shown that exogenous addition of bile acids to HBV-expressing cells can increase HBV replication.…”
Section: Hbv and Hccmentioning
confidence: 99%
“…HBV transcription is regulated by a complex network composed of cellular nuclear receptors and transcription factors, including hepatocyte nuclear factor 4α (HNF4α) (Curtil et al 2014, Quasdorff & Protzer 2010. FXR is a liver-enriched nuclear receptor activated by its natural ligands, bile acids.…”
Section: Perspectives On the Role Of The Receptor In Hbv Pathogenesismentioning
confidence: 99%
“…Apart from its crucial role in maintaining bile acids and cholesterol homeostasis, FXR also regulates the metabolism of lipid and glucose [79]. It has been shown that FXR is involved in various diseases such as metabolic disorders, hepatitis, arteriosclerosis and cancer [1014]. Thus, FXR has been considered as an important drug target after the deorphanization of FXR in 1999 [15].…”
Section: Introductionmentioning
confidence: 99%